The Janus Face of Lipids in Human Breast Cancer: How Polyunsaturated Fatty Acids Affect Tumor Cell Hallmarks. (2nd July 2012) - Chénais, Benoît; Blanckaert, Vincent
Abstract : For several years, lipids and especially n - 3 and n - 6 polyunsaturated fatty acids (PUFAs) receive much attention in human health. Epidemiological studies tend to correlate a PUFA-rich diet with a reduced incidence of cancer, including breast cancer. However, the molecular and cellular mechanisms supporting the effect of PUFAs in breast cancer cells remain relatively unknown. Here, we review some recent progress in understanding the impact that PUFA may have on breast cancer cell proliferation, apoptosis, migration, and invasion. While most of the results obtained with docosahexaenoic acid and/or eicosapentaenoic acid show a decrease of tumor cell proliferation and/or aggressivity, there is some evidence that other lipids, which accumulate in breast cancer tissues, such as arachidonic acid may have opposite effects. Finally, lipids and especially PUFAs appear as potential adjuvants to conventional cancer therapy.